The Role of the Vice President in the Republic of Indonesia's Administrative System (Post Amendment to the 1945 Constitution) - Trio Handoyo; Saefudin (Journal of Law Science, 2022)
The purpose of this study was to find out and analyze the role of the Vice President in the state administration of the Republic of Indonesia after the amendments to the 1945 Constitution. The data collection method used in this study was a literature study. The approach method used in this study is a normative juridical approach, namely research based on data obtained from laws and regulations. The data analysis method used is descriptive qualitative. The results of the research are as follows: (1) in the 1945 Constitution before the amendment, the role of the Vice President could be considered as a "spare tire", which functions as a substitute if the President is unable to, as stipulated in Article 4 paragraph (2) which reads: "In carrying out his obligations the President is assisted by a Vice President" and strengthened in Article 8 of the 1945 Constitution which reads: "if the President dies, stops, or is unable to carry out his obligations during his term of office, he is replaced by the Vice President until his term expires", as well as Deputy The President as the 'representative' who represents the President carries out presidential duties in matters delegated to him by the President; (2) the role of the Vice President after the amendments to the 1945 Constitution remained unchanged, because Article 4 of the 1945 Constitution did not undergo changes, while a fundamental change occurred in the election of the President and Vice President, namely in Article 6A paragraph (1), which reads "President and Deputy The president is elected in a pair directly by the people” and Article 7 of the 1945 Constitution (First Amendment) reads: "The President and Vice President hold office for five years, and after that they can be re-elected in the same position, only for one term of office". Regarding the dismissal of the President, it became clearer after the addition of Article 7A. if the President is dismissed due to proven criminal elements as contained in Article 7A, then the Vice President will replace the President's position and be sworn in as President in accordance with Article 8 paragraph (1) of the 1945 Constitution (Third Amendment); and (3) The functions, duties and powers of the vice president are highly dependent on the wishes of the president and the performance of the vice president depends on the ability and willingness of the person concerned, not because of standard and clear rules.